EXPLORING SOCIETAL INFLUENCES ON LINGUISTIC EVOLUTION: FINDINGS FROM LABOV’S PHONOLOGICAL ANALYSES (Web of Teachers: Inderscience Research, 2024)
This article primarily aims to examine the parallels and distinctions between William Labov's seminal investigations conducted in 1963 and 1972, focusing on phonological variations in speech sounds influenced by socio-cultural factors. Both inquiries underscore the profound influence of community dynamics and social interactions on nuanced pronunciation, despite their disparate geographical contexts. Analysis of the data gleaned from these investigations elucidates the pivotal roles played by social determinants such as ethnicity, socioeconomic status, age, and regional distribution in driving linguistic evolution and diversity. These case studies collectively demonstrate that comprehending the ramifications of sound change necessitates a thorough consideration of the social milieu in which it unfolds.